Review on Enterprise Resource Planning Implementation Roadmap: Project Management Perspective (Sains Humanika, 2014)
Enterprise Resource Planning (ERP) is multifaceted information system that aims to develop strong functionality, better performance, make better decisions and achieve a competitive advantage for organisations. However, the benefits of an ERP system cannot be easily acquired because it needs social and technological efforts to implement it. The practitioners need to be guided by a coherent roadmap for the implementation of ERP systems. For developing the coherent roadmap, therefore, the authors review recent ERP implementation roadmaps and highlight the research gap for the expansion of future works. An examination of the literature review reveals that recent ERP roadmaps do not apply a comprehensive project management, which contains of process group and the nine knowledge areas, as a methodology to implement a complex project. Thus, there is a need of research, which highlights the development of comprehensive ERP implementation roadmap, to assist the practitioners in implementing successful ERP systems.
Keywords: Enterprise resource planning; project management; roadmap